Analisis Kesalahan Berbahasa Teks Esai pada Laman mojok.co Edisi Maret 2025 sebagai Bahan Bacaan dan Informasi bagi Siswa SMA - Aprillia Puspita Sari; Sisya Nirmala Meida; Khairunnisa Ardhana; Al Mujahidatul Adilah; Afia Ananta Izmi; Asep Purwo Yudi Utomo; Riri Kumalasari; Antonius Edi Nugroho (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article analyzes language errors in essays written by high school students and published on the Mojok.co website in the March 2025 edition. It employs a descriptive qualitative approach with purposive sampling. Five essays were selected based on topic relevance and language difficulty levels appropriate for high school students. The analysis reveals language errors in four main categories: spelling, grammar, diction, and punctuation. Spelling errors are the most frequent, involving incorrect word forms that deviate from standard Indonesian spelling conventions, such as improper capitalization and the use of numerals where they are inappropriate. Grammar errors include issues in sentence structure, particularly in the incorrect placement of subjects and predicates. Diction errors often involve the use of inaccurate or informal vocabulary, while punctuation errors are evident in the misuse or misplacement of commas and periods. These findings suggest that students’ language proficiency in essay writing still requires improvement. To enhance their skills, the following recommendations are proposed: increasing students’ understanding of spelling, grammar, diction, and punctuation based on the General Guidelines for Indonesian Spelling; providing structured and continuous writing practice; incorporating technology such as spell checkers and grammar tools; and fostering an understanding of language variations, especially the differences between spoken and written language. Improving students’ writing skills is essential, as language errors can impede effective communication and undermine a writer’s credibility. This article aims to serve as a reference for both teachers and students in recognizing common writing errors and enhancing the overall quality of student essays.